A Perspective on Pediatric Respiratory Outcomes During California Wildfires Due to Smoke and PM2.5 Exposure - Naughten, Sarah M.; Aguilera, Rosana; Gershunov, Alexander; Benmarhnia, Tarik; Leibel, Sydney (Frontiers in Pediatrics, 2022)
As wildfires increase in prevalence and intensity across California and globally, it is anticipated that more children will be exposed to wildfire smoke, and thus face associated adverse health outcomes. Here, we provide a concise summary of the respiratory effects of California's wildfires on pediatric healthcare utilization, examine global examples of wildfire smoke exposure within the pediatric population and associated physiological effects, and assess the efficacy of metrics used to measure and communicate air quality during wildfires within the United States and elsewhere.